Pengaruh Profitabilitas, Likuiditas, Struktur Aktiva Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Chandra Raymond (JURNAL RISET AKUNTANSI TIRTAYASA, 2022)
This study aims to examine the factor that influence the capital structure, some of which areprofitability, liquidity, asset structure and firm size as moderating variabels than can influence thedependent and independent variabel variables. The data used in this study is secondary data from theIndonesia Stock Exchange. The sample used was 35 companies, in order to obtain 105 units of analysis.The results showed that Profitability, Liquidity, Asset Structure. Affect the capital structure. Meanwhile,capital structure can influence the dependent and independent variabels in this research